Differences in Growth and Yield Responses of Several Cayenne Pepper (Capsicum frutescens L.) Varieties in Cocoa (Theobroma cacao L.) Interrows - Nazatul Bairia; Hilda Pratiwi; Mizan Maulana (PT. Banjarese Pacific Indonesia, 2026)
This study aimed to analyze the response of several cayenne pepper varieties (Capsicum frutescens L.) on the growth and yield of cayenne pepper cultivated in the cocoa (Theobroma cacao L.) alley cropping system. The research was conducted from April to July 2025 at Mon Jambe Village, Jeumpa District, and the Kopbun Suka Tani Sejahtera Business Research Center, Kota Juang District, Bireuen Regency. The experiment employed a Randomized Block Design (RBD) with four varieties as treatments and three replications, resulting in 12 experimental units. The tested varieties were Rajo, Genie, Bara, and Tetra Hijau. Data were collected through observations of plant height, number of leaves, number of fruits, fruit weight, and fresh biomass weight, and were analyzed using analysis of variance (ANOVA) to determine differences among treatments. The results showed that the varietal factor had a highly significant effect on leaf number and a significant effect on fruit number and fruit weight. The Bara variety exhibited the most adaptive and productive performance under the cocoa alley cropping system, as indicated by superior vegetative growth and yield compared to other varieties. The novelty of this study lies in emphasizing that varietal selection is a key factor in optimizing the utilization of cocoa alley spaces for cayenne pepper cultivation. These findings are expected to provide a scientific basis for developing cayenne pepper cultivation technologies in cocoa alley systems and to serve as a reference for further research on adaptive variety development under such environmental conditions.